Investigating Periodic Table Interpolation for the Rational Design of Nanoalloy Catalysts for Green Hydrogen Production from Ammonia Decomposition - Parker, LA (Springer Science and Business Media LLC, 2024)
10.1007/s10562-023-04446-4